2016
DOI: 10.1002/ejoc.201600516
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 1,2,3,4,5,6,7‐Heptasubstituted Cycloheptatrienes through Cycloaddition Reactions of Substituted Cyclopentadienones

Abstract: Two schemes for synthesizing heptasubstituted cycloheptatrienes with various substituents in the ring are suggested. The first method is based on cycloaddition of 2,5‐dimethoxycarbonyl‐3,4‐diphenylcyclopentadienone with substituted cyclopropenes and allows cycloheptatrienes containing two or three electron‐withdrawing substituents in the molecule to be obtained. The second method employs a cascade reaction between a substituted cyclopentadienone and appropriate vinyldiazoacetates. It allows the number of elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…As a decomplexation of cyclopentadienones from their cyclopentadienylcobalt(I) complexes is possible by treatment with cerium ammonium nitrate, [28] the reaction provides a new access to substituted cyclopentadienone derivatives as building blocks for further syntheses of compounds such as interesting aromatic systems, [39,40] cycloheptatrienes, [41,42] anellated cyclopentanones, [43] norbornenones, [44] triptycenes, [45] and various heterocycles, [46,47] often by Diels‐Alder cycloadditions [48] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a decomplexation of cyclopentadienones from their cyclopentadienylcobalt(I) complexes is possible by treatment with cerium ammonium nitrate, [28] the reaction provides a new access to substituted cyclopentadienone derivatives as building blocks for further syntheses of compounds such as interesting aromatic systems, [39,40] cycloheptatrienes, [41,42] anellated cyclopentanones, [43] norbornenones, [44] triptycenes, [45] and various heterocycles, [46,47] often by Diels‐Alder cycloadditions [48] …”
Section: Resultsmentioning
confidence: 99%
“…[34] Two enantiomeric molecules are connected by a water molecule forming hydrogen bridges to the carbonyl oxygen atoms. with cerium ammonium nitrate, [28] the reaction provides a new access to substituted cyclopentadienone derivatives as building blocks for further syntheses of compounds such as interesting aromatic systems, [39,40] cycloheptatrienes, [41,42] anellated cyclopentanones, [43] norbornenones, [44] triptycenes, [45] and various heterocycles, [46,47] often by Diels-Alder cycloadditions. [48] In the course of our investigations with ferrocene systems it was shown that the anionic thia-Fries rearrangement does not take place with ferrocenyl mesylate or tosylate.…”
Section: Figurementioning
confidence: 99%
“…220,221 A different class of formal [3 + 4] cycloadditions was reported by Tomilov and co-workers using 1,2,3-trisubstituted cyclopropenes 329 and cyclopentadienones 330 to prepare heptasubstituted cycloheptatriene derivatives 331 (Scheme 47A). 222 Only a few examples of this class of compounds were prepared in useful yields and as single isomers. Nevertheless, the final location of the double bonds was substrate-dependent.…”
Section: Cycloaddition Reactions Of Cyclopropenes Involving Ring-clea...mentioning
confidence: 99%
“…Although the hepta-ester was not preparable directly via a Diels-Alder route, reaction of 2,5-dicarbomethoxy-3,4-diphenylcyclopentadienone with 1,2-dimethyl-3-carbomethoxycyclopropene did yield the corresponding cycloheptatriene, 47 , containing two methyls, two phenyls and three ester groups. Analogously, a number of cycloheptatrienes bearing multiple electron-withdrawing substituents–esters, nitriles and trifluoromethyl groups, as in 48 , were readily obtainable [ 58 ].…”
Section: Diels-alder Cycloadditions Of Alkynes or Triphenylcycloprmentioning
confidence: 99%